Preparation of a clay-modified carbon paste electrode based on 2-thiazoline-2-thiol-hexadecylammonium sorption for the sensitive determination of mercury - Dias Filho, Newton L. [UNESP]; Carmo, Devaney R. do [UNESP]; Gessner, Fergus; Rosa, André H. [UNESP] (Springer Nature, 2005)
A montmorillonite from Wyoming-USA was used to prepare an organo-clay complex, named 2-thiazoline-2-thiol-hexadecyltrimethylammonium-clay (TZT-HDTA-clay), for the purpose of the selective adsorption of the heavy metals ions and possible use as a chemically modified carbon paste electrode (CMCPE). Adsorption isotherms of Hg 2+, Pb 2+, Cd 2+, Cu 2+, and Zn 2+ from aqueous solutions as a function of the pH were studied at 298 K. Conditions for quantitative retention and elution were established for each metal by batch and column methods. The organo-clay complex was very selective to Hg(II) in aqueous solution in which other metals and ions were also present. The accumulation voltammetry of Hg(II) was studied at a carbon paste electrode chemically modified with this material. The mercury response was evaluated with respect to the pH, electrode composition, preconcentration time, mercury concentration, cleaning solution, possible interferences and other variables. A carbon paste electrode modified by TZT-HDTA-clay showed two peaks: one cathodic peak at about 0.0 V and an anodic peak at 0.25 V, scanning the potential from -0.2 to 0.8 V (0.05 M KNO 3 vs. Ag/AgCl). The anodic peak at 0.25 V presents excellent selectivity for Hg(II) ions in the presence of foreign ions. The detection limit was estimated as 0.1 μg L -1. The precision of determination was satisfactory for the respective concentration level. 2005 © The Japan Society for Analytical Chemistry.
Keywords: 2-mercaptothiazoline; Aluminum silicate; Anion; Bentonite; Carbon; Cetrimide; Divalent cation; Fresh water; Mercury; Sea water; Thiazole derivative; Thiazolidine derivative; Thyroidan; Adsorption; Calibration; Chemistry; Clay; Electrochemistry; Ion selective electrode; Oxidation reduction reaction; PH; Reproducibility; X ray diffraction; Adsorption; Aluminum Silicates; Anions; Bentonite; Calibration; Carbon; Cations, Divalent; Cetrimonium Compounds; Electrochemistry; Fresh Water; Hydrogen-Ion Concentration; Ion-Selective Electrodes; Mercury; Oxidation-Reduction; Reproducibility of Results; Seawater; Thiazoles; Thiazolidines; X-Ray Diffraction